Efektifitas Terapi Dzikir Untuk Menurunkan Tekanan Darah Pada Lansia - Mardiana; Irawati; Mas’ud, Alfian (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Objective: Hypertension is an increase in systolic blood pressure of more than 140 mmHg and diastolic blood pressure of more than 90 mmHg in two measurements with an interval of five minutes in a resting or calm state. Treatment or management of hypertension takes a long time, lifelong and continuous. Efforts made in the management of hypertension are in the form of pharmacological efforts (drugs) and non-pharmacological efforts (lifestyle modification) in addition to non-pharmacological therapy, namely dhikr therapy. To see the effectiveness of dhikr therapy in lowering blood pressure in the elderly suffering from hypertension. Methods: This literature study method is carried out by searching for the results of scientific publications in the range of 2014-2024, using data based google scholar. In the data based google scholar using the keyword